Efecto de la temperatura y secado en la viabilidad de polen almacenado de ochroma pyramide (Cav. Ex Lamb) (Balsa). año 2015 plan de mejoramiento - Jalca Zambrano, Ivonne Roció (2015)
This research was conducted in the plantations of the company Plantabal S.A. in Madera Seca 14 hacienda, located in the village of El Empalme, industry Banks, coordinate 1st 2'57.43'' south latitude and 79 ° West longitude 35'33.22'', with an area of 1.5 ha, a sample of 10 trees. The overall objective was to evaluate the effect of temperature and drying on the viability of O. pyramidale stored pollen, and make a proposal for a plan of genetic improvement through technical pollination directed. the best means of assessing the viability was determined by in vitro germination testing variants medium and Kwack Brewbaker (1963). The best way to measure the initial and post-storage viability was 10% sucrose, 30 mg L-1 boric acid, 430 mg L-1 calcium nitrate. The moisture content of fresh pollen O. pyramidale was calculated by thermogravimetric methods of 49.80% relative to its weight. The initial pollen viability was 65.62%. Pollen drying was performed in a climatic chamber at 29 ° C and 45% relative humidity (RH) for different times (60, 120, 180 and 240 minutes) pollen viability decreased gradually as the drying time increased , causing loss of 6.04% in pollen germination of O. pyramidale dried for 240 minutes. The samples were subjected 60', 120', 240' 180'y drying and stored at 5 ° (cooling), -20 ° C (freezing) and 196 ° C (cryo conservation) in eppendorf tubes for 45 days. The temperature and moisture content for optimal storage pyramidale O. pollen was at -196 ° C and 4.46% respectively.